Integration Manager Technology in ERP Application System (Case Study: PT. Argo Pantes, tbk) - Verri Kuswanto; Rudy Arijanto; Andi Leo (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
Many companies are already using ERP application systems but still do not utilize information technology as an interest in helping to achieve the goals of the company's vision. The process of inputting the ERP (Enterprise Resource Planning) application data that prioritizes data integration, the accuracy of the data from the master data to the daily transaction data is then recorded into a financial statement information for the related. From this research, the results achieved are the ERP application system in inputting data integration processes, master data and transaction data are able to validate the level of data accuracy with the help of the INTEGRATION MANAGER Technology which functions as the initial data matrix with ready-to-report data in an ERP application system, As for the TOWS Matrix Analysis external environment (threats and opportunities), and internal environment (weaknesses and strengths) in summarizing the conclusions reached are to help the accuracy of the data in the ERP application of PT. Argo Pantes, Tbk is more structured, more efficient, reduces input errors, input data is correct, accompanied by uptodate managerial decisions